Monensin Supplementation in Complete Rations For Kids - Biju Chacko (Department of Animal Nutrition, College of Veterinary and Animal Sciences, 1998)
An investigation was carried out to assess the influence of monensin supplementation in complete rations for kids. Thirty Malabari kids of three to four months of age were divided randomly into three equal groups (I, 11 and Ill). The animals were maintained on isoproteimic and isocaloric complete rations A, Band C containing eight, twelve and sixteen per cent crude fibre respectively for a period of 13 weeks'" (91 days). The rations were supplemented with monensin at the rate of 20 mg/kg. The weight gained by animals during the experimental period was highest in group I followed by groups 11 and III in the descending order, groups I and 11 showing significantly higher gains (P<O.Ol) than group Ill. This is suggestive of the positive influence of monensin in rations containing lower levels of crude fibre. Monensin did not appear to have any effect on body measurements viz., body length, chest girth and height at withers. The average daily dry matter (DM) intake of animals in group I was significantly higher (P<O.05) than group Ill, but